Mechanical performance, corrosion and tribological evaluation of a Co–Cr–Mo alloy processed by MIM for biomedical applications. (May 2020) - Herranz, Gemma; Berges, Cristina; Naranjo, Juan Alfonso; García, Cristina; Garrido, Ignacio
Abstract: In this study, the processing parameters mechanical performance, corrosion and tribological evaluation of a low carbon content Co–Cr–Mo alloy are discussed. The production of parts using the Metal Injection Moulding (MIM) process is optimized, specifically concerning the rheological analysis of the prepared feedstocks, the optimum choice of the powder loading and the design of the debinding and sintering cycles. The mechanical properties as regards hardness, tensile strength and bending strength, as well as fatigue tests and wear characterization, are discussed for the full densified specimens obtained. Additionally, corrosion behaviour with the different methods and electrolytic solutions that simulate the biological environment has also been investigated. This approach allows us to confirm that the low-carbon cobalt alloy processed by MIM exhibits an adequate equilibrium between its mechanical and corrosion behaviour, with a notable performance during fatigue and wear tests. In the light of these findings, the use of this material for biomedical applications is discussed. Graphical abstract: Image 1 Highlights: MIM is confirmed an attractive manufacturing method for biocompatible cobalt alloys. A remarkable fatigue performance is determined in the sintered parts. Low carbon MIM parts show improvements in corrosion behaviour. The wear resistance exhibited allow its use as biomaterial.